"Noah's Family Was on Lockdown": Multimodal Metaphors in Religious Coronavirus-Related Internet Memes in the Nigerian WhatsApp Space. (2nd October 2022) - Oyebode, Oluwabunmi O.; Unuabonah, Foluke O.
ABSTRACT: This paper examines the forms and functions of religious Internet memes that relate to Covid-19, with a view to identifying the conceptual metaphors that underlie the creation of the memes. The data, which consist of thirty religious Internet memes shared in the Nigerian WhatsApp space, are analyzed qualitatively using the categorization of religious Internet memes, and the concept of multimodal metaphors. The memes contain (non-)linguistic metaphors such as the picture of Biblical Noah's ark and expressions such as Noah's family was on lockdown, which reveal underlying conceptual metaphors such as LOCKDOWN IS A GODLY INSTRUCTION and COVID-19 IS A WAR. The memes are used to allay the fears of people in the face of the disease, and encourage adherence to lockdown orders, amongst others. The study concludes that the forms and functions of these religious memes assist in revealing the multimodal conceptual metaphors underlying the memes.